Identification of Rapeseed MicroRNAs Involved in Early Stage Seed Germination under Salt and Drought Stresses - Jian, Hongju; Wang, Jia; Wang, Tengyue; Wei, Lijuan; Li, Jiana; Liu, Liezhao (Frontiers in Plant Science, 2016)
Drought and salinity stresses are severe and wide-ranging abiotic stresses that substantially affect crop germination, development and productivity. Seed germination is the first critical step in plant growth and development. To comprehensively investigate small-RNA targets and improve our understanding of the miRNA-mediated post-transcriptional regulation network during rapeseed seed imbibition under drought and salt stresses, we constructed three small-RNA libraries from B. napus variety ZS11 seed embryos exposed to salt (200 mM NaCl, marked as S), drought (200 g L-1 PEG-6000, marked as D), and distilled water (marked as CK) during the imbibition process and sequenced them using an Illumina Genome Analyzer. A total of 11,528,557, 12,080,081 and 12,315,608 raw reads were obtained from the CK, D and S libraries, respectively. Further analysis identified 85 known miRNAs belonging to 31 miRNA families and 882 novel miRNAs in the three libraries. Six miRNA families—miR156, miR169, miR860, miR399, miR171 and miR395—were significantly down-regulated, whereas miR172 was significantly up-regulated, in the D library compared to the CK library. Only two miRNA families—miRNA393 and miRNA399—were significantly down-regulated in the S library compared to the CK library. Furthermore, putative targets for 336, 376, and 340 novel miRNAs were successfully predicted in the CK, D, and S libraries, respectively. A total of 271 miRNA families and 20 target gene families in rapeseed (including disease resistance protein (DIRP), drought-responsive family protein (DRRP), early responsive to dehydration stress protein (ERD), stress-responsive alpha-beta barrel domain protein (SRAP), and salt tolerance homolog2 (STH2)) were confirmed to be core miRNAs and genes involved in the seed imbibition response to salt and drought stresses. The sequencing results were partially validated by quantitative RT-PCR for both conserved and novel miRNAs and the predicted target genes. Our data suggest that diverse and complex miRNAs are involved in seed imbibition, which indicates that miRNAs are involved in plant hormone regulation and may play important roles during seed germination under salt- or drought-stress conditions.